Revisiting Québec's Jus Commune in the Era of the Human Rights Charters - Samson, Mélanie; Langevin, Louise (The American Journal of Comparative Law, 2015)
Québec is a distinct society because of its history, its legal system, and its values. Our analysis examines the delicate issue of the relationship between the Canadian Charter of Rights and Freedoms, the Québec Charter of Human Rights and Freedoms, and the Civil Code of Québec, the primary expression of Québec's jus commune, as noted in its Preliminary Provision. As of the nineteenth century, a doctrinal trend born of the desire to protect the integrity of the civil law system grew worried about the "disruptive" influence of the common law on the civil law and, more specifically, on the Civil Code of Lower Canada. The doctrine later expressed reluctance as to the entry of fundamental rights into Québec private law. The charters of rights were, and are sometimes still, perceived as disruptive elements, capable of distorting the Civil Code. We want to show that the influence of human rights philosophy on Québec's jus commune is not only inevitable but desirable. The Civil Code and, more broadly, Québec's jus commune, can only be enriched by respect for fundamental rights.